Groundwater Quality Assessment Based on Improved Water Quality Index in Pengyang County, Ningxia, Northwest China. Issue Volume 7:Issue S1(2010) (2010) - Pei-Yue, Li; Hui, Qian; Jian-Hua, Wu
Abstract : The aim of this work is to assess the groundwater quality in Pengyang County based on an improved water quality index. An information entropy method was introduced to assign weight to each parameter. For calculating WQI and assess the groundwater quality, total 74 groundwater samples were collected and all these samples subjected to comprehensive physicochemical analysis. Each of the groundwater samples was analyzed for 26 parameters and for computing WQI 14 parameters were chosen including chloride, sulphate, pH, chemical oxygen demand (COD), total dissolved solid (TDS), total hardness (TH), nitrate, ammonia nitrogen, fluoride, total iron (Tfe), arsenic, iodine, aluminum, nitrite, metasilicic acid and free carbon dioxide. At last a zoning map of different water quality was drawn. Information entropy weight makes WQI perfect and makes the assessment results more reasonable. The WQI for 74 samples ranges from 12.40 to 205.24 and over 90% of the samples are below 100. The excellent quality water area covers nearly 90% of the whole region. The high value of WQI has been found to be closely related with the high values of TDS, fluoride, sulphate, nitrite and TH. In the medium quality water area and poor quality water area, groundwater needs some degree of pretreated before consumption. From the groundwater conservation view of point, the groundwater still need protection and long term monitoring in case of future rapid industrial development. At the same time, preventive actions on the agricultural non point pollution sources in the plain area are also need to be in consideration.